Electrical, electronics, and digital hardware essentials for scientists and engineers - Lipiansky, Ed. (Hoboken, N.J. : Wiley, 2012)
"In order for all components of electric circuits to function flawlessly, electric device engineers need to be able to test, evaluate, and problem-solve the circuit board as a whole. Written by an expert with 25 years of working experience in Silicon Valley, this practical book walks readers through a wide variety of circuit analysis methods, discussing the pros and cons for each method, and how to evaluate it and solve everyday circuit analysis problems. Both basic and advanced tools are covered, along with trouble-shooting tips, practical examples, and numerous illustrations to facilitate comprehension"--
Includes bibliographical references and index.
Print version record.
Keywords: Electronic circuits; Electronic apparatus and appliances; TECHNOLOGY & ENGINEERING -- Electronics -- Circuits -- General; TECHNOLOGY & ENGINEERING -- Electrical; Electronic apparatus and appliances; Electronic circuits; Electronic books